Maritime Cultural Events in South Sulawesi an Analytical Review of Implementation and Its Impact - Syafruddin, Syafruddin; Dewi, Surya; Mulya, Rizky Adhy Satria (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Maritime Cultural Events in South Sulawesi have become a tourism magnet attracting global tourists and delivering significant economic impact to the local community. This article provides an analytical review of the implementation of maritime cultural events in South Sulawesi by analyzing the event's potential, factors supporting its success, and its impacts on the tourism sector and local cultural preservation. In this context, the study employs qualitative and descriptive approaches to delve into the dynamics of maritime cultural event implementation, including SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats influencing event development. The review identifies complexities and challenges involved while offering strategies to enhance promotion, protection, and development of this cultural heritage to ensure sustainability and long-term benefits for South Sulawesi.